Cardiovascular Adverse Events Complicating the Administration of Rituximab: Report of Two Cases. Issue 6 (November 2013) - Passalia, Caterina; Minetto, Paola; Arboscello, Eleonora; Balleari, Enrico; Bellodi, Andrea; Del Corso, Lisette; Molinari, Elisa; Ponassi, Irene; Oneto, Caterina; Sicbaldi, Vera; Ghio, Riccardo
Rituximab is a murine/human chimeric monoclonal antibody directed against the CD20 antigen. It is widely used in combination with polychemotherapy regimens for the treatment of hematological disorders. There is no evidence of direct cardiotoxicity of the drug but a few cases of cardiovascular adverse events have been reported in the literature. We report on two patients affected by stage IV non-Hodgkin lymphoma with bone marrow infiltration and peripheral blood involvement who experienced cardiovascular accidents temporally related to rituximab infusion. In both cases the monoclonal antibody was administered in association with a polychemotherapy regimen but administration was postponed several days later in order to avoid severe cytokine release syndrome because of the high tumor burden. The first case concerns an episode of atrial fibrillation in a patient with a diagnosis of small B-cell lymphoma. The episode happened immediately after rituximab infusion. In the second case there was an episode of chest pain associated with fever and chills during rituximab infusion in a patient with a diagnosis of mantle cell lymphoma. In both cases we noticed an unusual correlation between symptom recurrence and the speed of rituximab infusion. Both patients presented several cardiovascular risk factors but preliminary cardiac function assessment excluded signs of heart dysfunction. The pathogenesis of cardiovascular events during rituximab infusion remains unclear. A key role might be played by cytokine release from B cells as a consequence of rituximab activity. Moreover, pre-existing silent cardiac damage could be co-responsible for the clinical manifestations we reported. We consider our clinical experience relevant because it raises an issue of good clinical practice: despite rituximab's good tolerability profile, patients with cardiovascular risk factors should undergo accurate cardiac assessment so that silent heart disease can be detected. If the suspicion of cardiac damage is high, more extensive cardiac assessment is recommended.